FORMATION OF WAYS TO CREATE GLOBAL, REGIONAL AND PERSONAL EDUCATIONAL SPACES FOR BPR DOCTORS AND PHARMACISTS - Mintser, O.P.; Gykovskiy, O. M.; Grachova, T. I. (Medical Informatics and Engineering, 2023)
Background. The analyzed changes in the strategy of the development of the educational process, especially during the continuous professional development (CPD) of doctors and pharmacists, are catalyzed by modern information technologies. It is emphasized that the term "classroom", at least in its traditional sense, can no longer cover the place where learning takes place. Materials and methods. Results. The space in which learning takes place is no longer simply physical; it is also a virtual space. Accordingly, ideas about the educational process are changing. The purpose of the study was to focus attention on the inconsistencies between the modern requirements for the organization of CPD, the principles of quality control of the educational process, and the existing approaches to the planning and design of educational and methodological work. Conclusions. 1. The starting point for rethinking educational spaces to support BPR of doctors and pharmacists is a new vision of educational activities that these spaces should support. This vision must be based on a new theory of education, as well as on the recognition of the individual characteristics of the doctors and teachers who use these spaces. In addition, the special culture of the institution should be taken into account. Organizational structure and financial circumstances should also be considered. 2. Creation of the design of the educational space is a long-term project that should include the formation and maintenance of consensus among all participants in the teaching of educational materials, the vision of the educational program, and taking into account new technologies.